Diagnostic experience of intravenous leiomyomatosis with emphasis on conventional ultrasonography imaging: a single-center study - Ge, Zhitong; Wang, Yahong; Wang, Ying; Li, Wanying; Yang, Xiao; Li, Jianchu; Wang, Hongyan (Frontiers in Oncology, 2023)
Objective: Intravenous leiomyomatosis (IVL) is a rare and aggressive tumor type that has the potential to extend into the inferior vena cava (IVC) and is susceptible to be misdiagnosed and neglected. Despite its clinical significance, there is a paucity of research that has focused on the specific manifestations of IVL on ultrasonography.Therefore, this study aims to systematically analyze the specific ultrasound features of IVL and augment its diagnostic accuracy.Materials and Method: Prospective inclusion was granted to patients admitted to our hospital between December 2016 and March 2021 for an IVC-occupying lesion.Multi-modal ultrasonography, encompassing gray-scale and color Doppler, was conducted. Lesions were categorized as IVL or non-IVL based on pathological or follow-up data. Two ultrasound sonographers with over 5 years of experience read and recorded ultrasound data for all lesions, which were subsequently comparatively analyzed to identify specific signs of IVL.Results: A total of 284 patients diagnosed with IVC-occupying lesions were included in the study. The lesion types comprised of IVL (n=67, 23.6%), IVC thrombus (n=135, 47.5%), tumor thrombus of renal carcinoma involving the IVC (n=35, 12.4%), tumor thrombus of liver carcinoma involving the IVC (n=24, 8.5%), leiomyosarcoma of the IVC (n=14, 4.9%), and tumor thrombus of adrenocortical adenocarcinoma (n=9, 4.1%). The presence of "sieve hole" and "multi-track" signs was observed in 20 IVL lesions under the grey-scale modality, while both signs were absent in the non-IVL group (P<0.01). The study found no statistically significant differences in the presentation of "sieve hole" and "multi-track" signs under the grey-scale and color Doppler modalities in cases of intravascular lithotripsy (IVL) (P>0.05). Using these two signs as diagnostic criteria for IVL, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), miss rate, misdiagnosis rate, and accuracy were determined to be 29.9%, 100%, 100%, 82.2%, 70.1%, 0, and 83.5%, respectively (AUC ROC=0.649; 95%CI: 0.537-0.761).IVL exhibits distinct ultrasound presentations, including "sieve hole" and "multi-track" signs, which demonstrate high specificity and accuracy as diagnostic indicators. Furthermore, these signs are corroborated by pathological evidence and effectively distinguish IVL from other lesions occupying the IVC.